Accelerated programmes: what can the water sector learn from the power sector? - Shah, Tushaar; Singh, M. (2011)
The Government of India's 15-year old Accelerated Irrigation Benefits Programme has come under much-deserved criticism for all-round non-performance. The AIBP needs to be taken back to the drawing board and redesigned, based on the Accelerated Power Development and Reform Programme, which encourages and supports states to undertake management reform, promote accountability, restructure incentives and improve all-round performance of power utilities. This will accelerate irrigation benefits more than simply funding more dams and canals as the AIBP has done all along.